Health status profile of climacteric women - Santos, Roberta D.S.; Carvalho, Flávia G.D. [UNESP]; Lima, Tatiana P.; Viegas, Riana L.; Faria, Angélica; Suen, Vivian M.M.; Navarro, Anderson M.; Iannetta, Renata; Nonino, Carla B.; Marchini, Julio S.; Iannetta, Odilon (My University, 2012)
Study design: Retrospective analysis of medical records. Purpose: This study aimed to determine the prevalence of obesity, diabetes mellitus, hypertension and dyslipidemia in a group of climacteric women. Methods: Study of the first patients treated at the Menopause Clinic (ACLI), Department of Obstetrics and Gynecology, School of Medicine of Ribeirão Preto (USP), from 1983 to 2007. Data on weight, height, BMI, biological group, diagnosis of hypertension, diabetes and dyslipidemia was collected from February/2008 until April/2008. Results: From 1983 until 2007, 400 patients were followed up, and 272 had their records registered. Of these 272 patients, 628 were selected queries, and therefore, on average, each woman had three returns. Women over the age of 29 and maximum of 80 years and median BMI above 25kg/m2. The prevalence of diabetes, hypertension and dyslipidemia was respectively 32%, 68% and 54%. The prevalence of NCDs and BMI was higher for the later groups. Conclusion: Climacteric women treated at a hospital level care center showed a worsening of the BMI and the prevalence of noncommunicable chronic diseases over time, which is urging a closer look at health professionals in this population group.
Keywords: Climacteric; Diabetes mellitus; Dyslipidemias; Hypertension; Menopause; Obesity; adult; aged; body height; body mass; body weight; chronic disease; climacterium; diabetes mellitus; dyslipidemia; female; follow up; health practitioner; health status; hospital care; human; hypertension; major clinical study; medical record review; obesity; prevalence; review